Yellow and red ochre pigments from southern Portugal: Elemental composition and characterization by WDXRF and XRD - Gil, M. (2012)
Three different yellow and red ochre pigments geological sources from Alentejo—Terras rossas, schist units and weathered iron ore deposits—were studied by elemental and phase analysis complemented with Munsell and CIELAB colour parameters. Central aims were to underline the mineralogical and chemical distinctiveness of natural pigment sources and establish a connection between local geology and use of speciﬁc colour pigments in traditional lime wash mural paintings. According to the chemical composition the Fe abundance is 6 times higher than average crust values. The Terras Rossas are characterized by higher Ca contents. In yellow and red schists, phyllosilicates are major minerals, so pigments from these units areenriched in K and Rb. Besides Fe, the pigments from weathered ores are enriched in metals like Pb, As, Cu, and Zn, which can be used as ﬁngerprints.